Microbiological and biochemical studies of traditional medicinal plants used in Limpopo Province for anti-micobacterium tuberculosis activity - Komape, Nancy Patience Motlalepula (University of Limpopo, 2019)
Tuberculosis (TB) is one of the top ten diseases that causes morbidity and mortality worldwide. Although TB is curable, the main problem currently with TB is development resistance to the current chemotherapy. Medicinal plants, as a source of drugs, have been found to cause less or no resistance. Medicinal plants are studied and considered for their efficacy and safety because they possess bioactive compounds with various biological activities. The aim of the study was to isolate and characterise bioactive compounds from selected seven plant species [A. dimidiata (LNBG 1969/46), A. afra (LNBG 2010/27), Z. capense (LNBG 1969/100), C. herorense (LNBG 1977/71), L. javanica (LNBG 1969/460), E. camaldulensis and C. lemon (UNIN 12330)] with activity against Mycobacterium smegmatis, Multi- drug resistant tuberculosis starain and H37Rv Mycobacterium tuberculosis strain. It was also imperative to determine whether crude extracts, sub- fractions of the extracts and the isolated bioactive compounds are cytotoxic or not. Leaves of the seven selected plants were collected from South African National Botanical Institute (SANBI) at Nelspruit, Mpumalanga Province, South Africa. The leaves were dried and milled to fine powder. The leaves of each plant were extracted using solvents of varying polarity (i.e. hexane, dichloromethane, acetone and methanol). Phytochemical screening was done using Thin Layer Chromatography (TLC) developed in three mobile phases varying in polarity and then sprayed with vanillin sulphuric acid in methanol heated at 110oC for optimal colour development. Qualitative antioxidant activity was determined by using 1,2- diphenylpicryl hydrazyl (DPPH) assay on TLC plates. Antimycobacterial activity for all the plant extracts was done using bioautography assay in qualitative analysis of the active compounds and for quantitative analysis, the microplate dilution assay was used. The plants which showed better activity (C. lemon, C. hereroense and A. dimidiata) with the microplate dilution assay and bioautography were further subjected to solvent- solvent fractionation as the first step towards isolation of bioactive compounds. Synergistic, additive, indifferent and antagonistic effects of the crude extracts combinations of the three selected plants was determined. The combinations where A. dimdiata was also part of the combinations frequently showed synergistic effect. On the other hand, with the combinations of C. hereroense and A. dimdidata (CH-AD) there was no antagonistic effect observed. The combinations of crude extracts of C. lemon and A. dimidiata all showed synergistic effect, except for only three combinations. Based on the synergistic effect observed and the bioactivity on the bioautography and microplate dilution assay of the sub- fractions, A. dimidiata was chosen for further analysis for antimycobacterial activity using the MDR- TB strain and M. tuberculosis H37Rv strain. The sub- fractions of A. dimidiata with the most activity were hexane and butanol. Hexane and butanol fractions both showed good MIC activity against the TB isolated M. tuberculosis field strain and H37Rv strain of 0.47 and 031 mg/ml, respectively. Butanol fraction was further taken for isolation using open colum chromatography doing bioassay guided isolation. The isolated compounds, together with the crude were tested for their biological activity using MTT assay to determine their cytotoxicity and antimycobacterial activity assay to confirm their activity against M. smegmatis and M. tuberculosis. Cytotoxicity assay showed that the crude extracts of A. dimidiate were toxic against the Vero kidney cells and the subfractions (i.e. butanol and hexane) became moderate to non-toxic and one compound (oleanolic acid) from the butanol sub-fraction was non- cytotoxic. This indicates that the isolation of the crude extracts tends to become non- toxic to the cells. The study suggests the use of pure compounds to fight against TB as compared to crude extracts since they are both bioactive and non- cytotoxic. Crude extracts combinations were effective in killing Mycobacterium as compared to single crude extracts. The present study recommends the use of A. dimidiata plant leaves crude extracts combinations as they mostly exhibit synergistic effect. Furthermore, Mycobacterium and also contain non- cytotoxic antimycobacterial compound (oleanolic acid). The study serves as a scientific proof for the use of this plant in traditional medicine for TB treatment.
Thesis (Ph. D. (Microbiology)) --University of Limpopo, 2019
Keywords: Tuberculosis; Use of traditional medicinal plants; Tuberculosis treatment; Medicinal plants - Biotechnology; Tuberculosis - Alternative treatment